Theoretical grounds for development of new generation state standards of vocational education - Luk’yanenko, G (Professional Pedagogics, 2011)
The article studies conceptual approaches as to vocational education and training modernizationthat are stipulated by socio-economic changes and swift development of market relations in thesphere of labor. The vocational education renovation demands reforming of both the model of qualifiedworkers training, its transition from responding to advance and regulation basis viz standards of vocationaltraining. According to the author, development of educational standards will be implemented onthe basis of principles of solidity and flexibility, module-competence approach being the leading one
Keywords: vocation education and training standards of a new generation; principles of solidity and flexibility; module-competence approach